NATURE OF THE LAYERING IN FERRODOLERITE SILLS - Marakushev A.A.; Kaminskiy A.D. (My University, 1990)
Unique petrographic material on layered dolerite sills was obtained on the Siberian craton when its cover was drilled during field work by Yeniseyneftegazgeologiya. Here we shall consider data on the Anakit layered sill, To model the development of the Anakit sill, we recalculated the chemical analyses of its rocks to 100 weight percent water-free matter and plotted them on the corresponding chemical composition diagrams. This clearly revealed the layered structure of the sill, which consists of 11 layers - the products of independent magma differentiation, marked with the roman numerals I to XI in consecutive order from the bottom up. The Anakit sill in its general mode of differentiation can be clearly subdivided into three parts - basal (I), intermediate (II to V) and apical (VI to XI).